Cartilage Restoration Practical Clinical Applications - Farr, Jack.; Gomoll, Andreas H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Attempting to bridge the gap between the science and art of cartilage restoration, Cartilage Restoration: Practical Clinical Applications combines an overview of clinical research and methodologies with clinical cases to help guide the orthopedic treatment and care of patients presenting with cartilage issues. With chapters written by internationally-renowned orthopedic surgeons, topics include an overview of current surgical options, debridement and marrow stimulation, autograft plug transfer, allografts, cell therapy, and meniscal issues. Cartilage Restoration is a valuable resource for orthopedic surgeons, residents, and fellows.
Learning from the Evolution of Cartilage Restoration -- The Osteochondral Unit -- Imaging of Articular Cartilage -- General Treatment Algorithm for Cartilage Defects -- Tibiofemoral Malalignment -- Tibiofemoral Patholaxity -- Patellofemoral Considerations: Pain, Instability, Chondrosis and Alignment -- Meniscal Considerations in Cartilage Surgery -- Approaching Complex Cases -- Debridement and Marrow Stimulation -- Osteochondral Autograft Transfer -- Osteochondral Allograft -- Autologous Chondrocyte Implantation (ACI) -- Arthroscopic MACI -- Particulated/Minced Cartilage -- Osteotomy for Tibiofemoral Malalignment -- Patellofemoral Osteotomies -- Meniscal Transplantation Techniques -- Alternatives to Meniscus Transplantation Outside the United States.
Keywords: Medicine; Orthopedic surgery; Rheumatology; Sports medicine; Medicine & Public Health; Surgical Orthopedics; Sports Medicine; Rheumatology